PENDIDIKAN SEBAGAI INVESTASI MASA DEPAN MASYARAKAT DESA - Kristoforus Dowa Bili (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
Human life is dynamic. In its dynamics, education is one sector that influences the quality of human life in the world, including rural communities. Thus, Education is the spearhead of a country [province, district, sub-district, and village]. Through this idea, education must be the main concern of all citizens, especially the villagers. With primary attention to education, the progress achieved through it can be experienced. The reality shows a significant gap when villagers have not put education as the spearhead of progress. As a result, financial use is prioritized for various non-educational matters, one of which is culture. This has an effect on the low attention to the cost of education so that it places villagers in a vortex of lagging. This scientific paper aims to make villagers understand the importance of education as the spearhead of the progress of a region; understand the type of education or the Three Education Center in Indonesia; understand the benefits or uses of education; and realize